The Effect of Shuttle Run and Zig-Zag Run Training On Dribbling Skills - Rachmat Hidayat; A Heri Riswanto; M Iqbal Hasanuddin (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2021)
The shuttle run exercise is a form of exercise that can improve agility. The zigzag run exercise is a form of agility training that involves the use of bollards and stakes. UM Palopo futsal players must have good dribbling skills. The conditions experienced by UM Palopo futsal players still often make mistakes in their dribbling skills. The lack of skills possessed by UM Palopo futsal players is due to the lack of agility training models that can support the achievements of futsal players. This study aims to reveal the effect of shuttle run and zig-zag run training on dribbling skill. The method used is a quasi-experimental (quasi-experimental). The population is 20 people from UKM Futsal UM Palopo. The sampling technique is purposive sampling. The data collection technique used the dribbling skill instrument and was analyzed by using the sig level t test. = 0.05. The results of the analysis show that there is a significant effect of shuttle run with a value of tcount value of 20,904 > ttable of 1,812 and pvalue that is 0.000 < 0.05. Zig-zag run with tcount value of 26,826 > ttable of 1,812 and pvalue that is 0.000 < 0.05. The improvement in shuttle run training with an average value of 17.55 and zig-zag run training with an average value of 15.61 and a significant value of 0.000 < 0.05. It can be concluded that the zig-zag run is more effective in improving dribbling skills.